2009
DOI: 10.1523/jneurosci.5255-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Aminergic Modulation of Distinct Spinal Locomotor Circuits and Their Functional Coupling during Amphibian Metamorphosis

Abstract: The biogenic amines serotonin (5-HT) and noradrenaline (NA) are well known modulators of central pattern-generating networks responsible for vertebrate locomotion. Here we have explored monoaminergic modulation of the spinal circuits that generate two distinct modes of locomotion in the metamorphosing frog Xenopus laevis. At metamorphic climax when propulsion is achieved by undulatory larval tail movements and/or by kicking of the newly developed adult hindlimbs, the underlying motor networks remain spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…In embryos, 5-HT only affects the burst duration without change in the frequency (Sillar et al, 1992), while in premetamorphic tadpoles it decreases the frequency (Rauscent et al, 2009). The mechanisms responsible for the change in the actions of 5-HT during development are not yet clear.…”
Section: Influence Of 5-ht On the Locomotor Network In Other Preparatmentioning
confidence: 96%
“…In embryos, 5-HT only affects the burst duration without change in the frequency (Sillar et al, 1992), while in premetamorphic tadpoles it decreases the frequency (Rauscent et al, 2009). The mechanisms responsible for the change in the actions of 5-HT during development are not yet clear.…”
Section: Influence Of 5-ht On the Locomotor Network In Other Preparatmentioning
confidence: 96%
“…There was also evidence for direct functional interactions between the spinal locomotor CPGs themselves (see also Combes et al, 2004;Rauscent et al, 2009), as indicated by the axial VR burst-timed modulation of both left and right Ext nerve burst discharge, and the reciprocal augmentation of axial burst amplitudes during each Ext burst (Fig. 4).…”
Section: Locomotion-related Ocular Movements At Metamorphic Climaxmentioning
confidence: 92%
“…2B). After isolation in vitro, the brainstem/spinal cord of such animals during this transitional period continues to spontaneously generate the motor burst patterns that would normally drive axial or hindlimb muscle contractions underlying the two locomotor modes in vivo (Combes et al, 2004;Beyeler et al, 2008;Rauscent et al, 2009). As seen in the extracellular recordings of Fig.…”
Section: Bimodal Fictive Locomotion At Metamorphic Climaxmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have proposed that different neuromodulators which activate the same ionic current or modify similar synaptic properties within a network can produce distinct network outputs by targeting distinct sets of neuron types (Swensen and Marder, 2001; Marder and Thirumalai, 2002; Rauscent et al, 2009; Calabrese et al, 2011). From this perspective, there appears to be little advantage for distinct neuromodulators employing convergent actions on the same voltage-gated current in the same neuron.…”
Section: Introductionmentioning
confidence: 99%